Періодизація творчості Йова Кондзелевича - Откович, Т. (Інститут народознавства НАН України, 2008)
In the article goes speech about creation of Yova Kondzelevicha, the variant of systematization of his works and their distributing is examined on separate periods at times and by the place of creation. Also in the article the attempts of atribucii are given recently works which after the row of signs can belong to the Yova Kondzelevicha raceme.